2018
DOI: 10.1128/aac.02656-17
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Metabolic and Lipid Profiles in Polymyxin-Resistant Pseudomonas aeruginosa

Abstract: Multidrug-resistant presents a global medical challenge, and polymyxins are a key last-resort therapeutic option. Unfortunately, polymyxin resistance in has been increasingly reported. The present study was designed to define metabolic differences between paired polymyxin-susceptible and -resistant strains using untargeted metabolomics and lipidomics analyses. The metabolomes of wild-type strain K ([PAK] polymyxin B MIC, 1 mg/liter) and its paired mutant strains, PAK and PAK (polymyxin B MICs of 16 mg/liter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 60 publications
(71 reference statements)
7
50
0
Order By: Relevance
“…The protein encoded by PA4775 has no homologue within the databases but the open reading frame (ORF) is cotranscribed with speE2 (28) and is required for conferring resistance to dendrimers. Indeed, the speD2 operon was recently described as being responsible for the synthesis of norspermidine (29,37,38). However, addition of spermidine or norspermidine, carrying three amine groups, had no effect on AMP activities.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by PA4775 has no homologue within the databases but the open reading frame (ORF) is cotranscribed with speE2 (28) and is required for conferring resistance to dendrimers. Indeed, the speD2 operon was recently described as being responsible for the synthesis of norspermidine (29,37,38). However, addition of spermidine or norspermidine, carrying three amine groups, had no effect on AMP activities.…”
Section: Discussionmentioning
confidence: 99%
“…The modification of lipid A, such as the addition of L-Ara4N, phosphoethanolamine, and galactosamine, was linked to homogeneous colistin resistance in various bacteria (12,31). In P. aeruginosa, lipid A is modified with the addition of L-Ara4N through the pmrHFIJKLM operon and under the control of pmrAB and phoPQ, which leads to colistin resistance (32). However, there have been few studies of lipid A structure with respect to colistin heteroresistance.…”
Section: Colistin (Hetero)resistance In Pseudomonas Aeruginosamentioning
confidence: 99%
“…8 The pmrB mutant of P. aeruginosa showed a significant metabolic perturbation in the total intracellular lipid level, the methionine salvage cycle, and synthesis of spermidine. 5 Resistance can be mediated by the addition of positively charged arabinosamine through the action of the arnBCADTEF operon. The results achieved in the present research were consistent with a previous report, in which the complex regulation of LPS modification involved the participation of at least 4 two-component regulatory systems in P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that Gramnegative pathogens exhibited resistance mechanisms of AMPs, including proteolytic degradation of AMPs, shielding of the bacterial surface, modification of the bacterial outer membrane, pumping AMPs into or out of the cell, downregulation of AMP expression, 3,4 diverse genetic alterations, and alterations of amino acids and carbohydrate metabolism. 5,6 Some bacteria (e.g., P. aeruginosa) also could develop resistance to a number of AMPs, such as polymyxin, 7 and reports on resistance of polymyxins in P. aeruginosa have increased. A growing number of P. aeruginosa strains demonstrated resistance to AMPs due to mutations in twocomponent regulatory systems (e.g., PhoPQ and PmrAB).…”
Section: Introductionmentioning
confidence: 99%